Climate Change Responses in the Saudi Maritime Sector: A Comprehensive Survey Study - Shadi Alghaffari; Aya ElBauomy; Alessandro Farina; Kareem Tonbol (Future Transportation)
This research investigates the Saudi marine sector’s response to climate change. In particular, it assesses industry stakeholder awareness, attitudes, and actions concerning climate-related challenges. A complete survey was distributed to a varied range of industry participants, including executives, managers, seafarers, and academics, to assess their understanding and involvement. The research indicates moderate levels of awareness and engagement, and significant challenges, including financial limitations, a lack of experience and knowledge, and insufficient regulatory support, to implementing more sustainable practices. The study also mentions ongoing attempts to satisfy International Maritime Organization (IMO) requirements, while present mitigating techniques have limited efficacy. Compared to other regions, Saudi Arabia mostly depends on fossil fuels, which poses specific difficulties in the transformation of sustainable maritime practices. The study identifies current strategies and proposes prospects such as raising financial assistance, and the adoption of innovative technologies. These findings are critical to providing the link between the Saudi marine sector and the climate targets, as well as the Saudi Vision 2030.